TOXIC PARENTING AND ITS IMPACT ON CHILDREN'S LANGUAGE ETHICS - Riza Khairani Harahap; Daulay, Annisa Arrumaisyah (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
This study focuses on examining parental practices in raising children. Parenting patterns encapsulate the methods employed by parents to nurture, guide, and lead their children within the family context. A recently emerged concept known as "toxic parenting" refers to a parenting style that is deemed detrimental due to the improper treatment administered by parents. Such a parenting pattern can impede a child's growth and development, leading to feelings of depression, stress, and anger, which may manifest in the use of inappropriate language and even traumatic experiences. The objective of this research is to explore the relationship between parenting styles and the ethical use of language by children. To achieve this goal, descriptive qualitative methods, including data analysis, interviews, and observations, were employed. The analysis revealed that toxic parenting is an inappropriate parenting style, as it has adverse effects on a child's future growth and development, particularly in terms of language ethics. Notably, toxic parenting fosters the use of impolite language among children in their social environment. Furthermore, this parenting pattern disrupts familial bonds. It is imperative for parents to provide adequate care for their children, as the use of inappropriate language by parents leads to their children resulting in negative consequences, such as the adoption of unsuitable language by children, both among their peers and others. Consequently, it is essential to avoid this type of parenting approach.